(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Robotics is developed very rapidly in the last two decades. Robotics has found wide range of applications in today’s world. The development of technology has opened the new doors for the replacement of human by the machines. The robotics development is not only limited to the military applications but it has found several applications in domestic purposes also. The research was started with the basic robot model in 1961 from the metal pieces connected together; today it results in the replacement of the human by robot. The robots have optimized many industrial applications and have provided the better efficiency by reducing the errors and the time requirements. In this manuscript, authors have presented the overview of the research carried out on the robot systems utilised for the elderly and disabled human beings.